ANALISA PREDIKSI KEBANGKRUTAN METODE ALTMAN Z”SCORE PADA PT HANSON INTERNATIONAL, Tbk - Safri Safri (JURNAL MITRA MANAJEMEN, 2012)
AbstactThe purpose of this study was to predict bankruptcy PT Hanson International, Inc., using the methodof Altman Z (Zeta) - Score. Data collection techniques to the calculation are taken from the company'sfinancial statements for 5 (five) years, the financial statements in the form of balance sheets and incomestatement. The method used is the method of Altman Z “'Score, because the object of research is a publiccompany. And corporate accounting period is the accounting period 2006 to 2010.Decision making based on the calculation of the equation Altman Z "score = 6.56 + 3.26 X1 + 6.72 X2+ 1.05 X3 X4, which is calculated by excel Altman Z-Score Calculation. Of the financial statements havebeen prepared and audited company, data is processed with grouped into 4 (four) the ratio of Z "ScoreAltman. And the sum of these calculations and the cut off or interpretation table Altman used for decisionmaking.The results showed that PT Hanson International, Inc. during 2006 to 2010 in the position of the zonewhere the potential for bankruptcy in 2006 Z "Score = -6.91, in 2007, Z" Score = -10.37, in 2008 Z "Score =-2252.17, in 2009 Z" Score = -5425.75, and in 2010 Z "Score -32.22. So every year of research, thecompany is in the zone Z "Score <1.1, or in other words, PT Hanson was at the level Distress Zone (zoneof insolvency). Thus the analysis of Altman Z "Score with the formula the ratio of net working capital to totalassets, retained earnings to total assets, Earning before interest to total assets and market value of equityto book value of debt can be concluded that the PT Hanson International, Inc. is located at unsafe position(zone of bankruptcy)Key words: financial statements of PT Hanson International, Inc., the method of Altman Z”Score,